Facilitating identification of minimal protein binding domains by cross-linking mass spectrometry. Issue 1 (December 2017) - Liu, Qingyang; Remmelzwaal, Sanne; Heck, Albert; Akhmanova, Anna; Liu, Fan
Abstract Characterization of protein interaction domains is crucial for understanding protein functions. Here we combine cross-linking mass spectrometry (XL-MS) with deletion analysis to accurately locate minimal protein interaction domains. As a proof of concept, we investigated in detail the binding interfaces of two protein assemblies: the complex formed by MICAL3, ELKS and Rab8A, which is involved in exocytosis, and the complex of SLAIN2, CLASP2 and ch-TOG, which controls microtubule dynamics. We found that XL-MS provides valuable information to efficiently guide the design of protein fragments that are essential for protein interaction. However, we also observed a number of cross-links between polypeptide regions that were dispensable for complex formation, especially among intrinsically disordered sequences. Collectively, our results indicate that XL-MS, which renders distance restrains of linked residue pairs, accelerates the characterization of protein binding regions in combination with other biochemical approaches.